2017
DOI: 10.1038/s41598-017-08174-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of macula in eyes of healthy children 8 to 16 years old using optical coherence tomography angiography

Abstract: The purpose of the present study was to investigate the vascular flow density (VD) of macular superficial (SCP), deep capillary plexus (DCP), and choriocapillaris and the size of the foveal avascular zone (FAZ) area in healthy children using optical coherence tomography angiography (OCTA). The potential associations of age, sex, intraocular pressure, body mass index, spherical equivalent, and axial length with OCTA parameters were also investigated. A total of 75 eyes from 75 healthy children were included for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
55
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 39 publications
14
55
8
Order By: Relevance
“…These findings are consistent with previous studies on adults [7-9]. The study by Zhang et al [13], which examined Chinese children aged 8–16 years also showed a smaller FAZ surface area in boys in the SCP. However, to the best of our knowledge, the present work is the first study to show a smaller FAZ surface area in the DCP in boys compared with girls and to report a gender difference in FAZ dimensions in European children with and without vascular pathology.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These findings are consistent with previous studies on adults [7-9]. The study by Zhang et al [13], which examined Chinese children aged 8–16 years also showed a smaller FAZ surface area in boys in the SCP. However, to the best of our knowledge, the present work is the first study to show a smaller FAZ surface area in the DCP in boys compared with girls and to report a gender difference in FAZ dimensions in European children with and without vascular pathology.…”
Section: Discussionsupporting
confidence: 83%
“…It was previously shown in adult subjects [10], and the same trend was noticed in Chinese children by Zhang et al [13]. However, unlike the present study, they failed to show a significant difference.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In the literature, a study by Liu et al 21 reported moderate correlation for the superficial capillary plexus density (Spearman’s correlation r=0.402) between the fellow eyes, while another article by Zhang et al 23 used Pearson’s correlation and found the foveal vessel density has high correlation (r=0.888). There are two possible reasons for the inconsistency between our results and the literature.…”
Section: Discussionmentioning
confidence: 99%